THE LEGAL AND REGULATORY ASPECT OF LIBERALIZATION IN CORPORATE FINANCE. DESIGNING STRICTER REGULATION IS DESIRABLE TO PREVENT FINANCIAL DOWNTURN, WHICH RESULTS IN ECONOMIC RECESSION. ISLAMIC FINANCE PROSPECTIVE - Gofurova, Robiya (Educational Research in Universal Sciences, 2023)
The purpose of this report is to examine the legal and regulatory aspect of liberalization in corporate finance and to discuss whether designing stricter regulation is desirable to prevent financial crises that brins to economic recession in line with Islamic Finance industry. The report will begin by defining liberalization in corporate finance, followed by a discussion of the legal and regulatory framework governing corporate finance. The report will then examine the impact of liberalization on financial crises, how it influenced Islamic financing sector, and finally, it will evaluate the arguments for and against designing stricter regulations.